SOLUSI PENGENTASAN KEMISKINAN PERSPEKTIF ALQURAN - Nagga, Jumaedi (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
Poverty is a serious problem faced by humanity, including in Indonesia. Poverty that is left without a solution will threaten the faith, morals, and thoughts of each individual. More than that, poverty is also very vulnerable to threatening social and national life by causing horizontal conflicts in society. The Quran as a syifa’ is expected to be able to provide several solutions to alleviating existing poverty. This research aims to analyze the solutions offered by the Quran regarding poverty alleviation. This research adopts qualitative research whose data comes from the Quran. Quran verses are grouped into relevant themes. Grouping was carried out by reviewing studies by previous scholars. Research finds that empowering potential through work, creating social justice, appropriate use of resources, and distribution of wealth are the Quran’s solutions to poverty. The Quran not only emphasizes the importance of each individual’s hard work but at the same time also opposes the elite’s monopoly on economic resources and encourages the creation of universal social justice.